Changes in self-reported sleep and cognitive failures: a randomized controlled trial of a stress management intervention - Ligaya Dalgaard; Anita Eskildsen; Ole Carstensen; Morten Vejs Willert; Johan H Andersen; David John Glasscock (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: This study evaluated the effectiveness of a stress management intervention combining individual cognitive behavioral therapy (CBT) with a brief workplace intervention on self-reported measures of sleep and cognitive functioning among patients on sick leave due to work-related stress complaints. METHODS: Participants were patients referred to the regional Department of Occupational Medicine. Inclusion criteria were (i) sick leave due to work-related stress complaints and (ii) a diagnosis of adjustment disorder/reactions to stress or mild depression. Participants (N=137) were randomized to either an intervention (N=57) or control (N=80) group. The intervention comprised six sessions with a psychologist and the offer of a small workplace intervention. Questionnaires were answered at baseline and after 4, and 10 months. RESULTS: Symptoms were significantly reduced over time in both groups but there was no significant treatment effect on sleep or cognitive outcomes at any time point. From 0-4 months, there was a tendency for larger improvements in the intervention group with regards to sleep and cognitive failures in distraction. Although neither was significant, the results came close to significance depicting a small effect size (Cohen's d) on sleep complaints and distractions (but not memory). CONCLUSIONS: The specific intervention was not superior to the control condition in reducing symptoms of sleep problems and cognitive difficulties at any time point during the 10-month follow-up period. Substantial improvements in symptoms over time were seen in both groups.